A água utilizada para consumo humano no município de Atalaia, Alagoas : uma análise de seu gerenciamento à luz da política de saúde ambiental. - Albuquerque, Verônica Peixoto de (2007)
Environmental unbalance caused by human action becomes evident, among other ways, by the contamination and inequality of water distribution. Water for human consumption is a means to the maintenance of health, as it is regarded as an essential social right and recognized as an indicator of human development. On the other hand, the quality of water is a determiner of hydric-coveyed diseases. In this context, policies of environmental health arise as an improvement of the local system of public health (Sistema Único de Saúde SUS), acting both in the scenarios formed by social environmental conditions and life styles, in order to improve education in education and environmental quality which entail lasting effective results for health than the mere providing of assistant services.The present work was developed with the aim at analyzing the water for human consumption in the municipality of Atalaia, state of Alagoas, on the grounds of the environmental health policy, identifying the sources of water for consumption and presenting the characterization and concerns of the social players involved in the management. It also presents both control data analysis and surveillance of water quality between 2005 and 2006. The lack of environmental protection related to the water sources for consumption was observed not due to omission of both the surveillance boards and the civil society and resulting in a continuous deterioration, which entails difficulties in the water treatament thus implying its low quality. In what concerns the role of the social players envolved, non-integrated articulation, reduced participation, and inexisting social control were observed. This study shows the municipality s difficulties in exerting actions of control in accordance with the rules of the Health Ministry in that it involves a more complex transformation provide more effective and integrated participation and social control. In this sense, effective changings have become necessary which will guarantee to population the right to consume good water.